An integration of quadripartite and helplessness-hopelessness models of depression using the Turkish version of the Learned Helplessness Scale (LHS). Issue 5 (2nd September 2020) - Boysan, Murat
ABSTRACT: The main focus of this study was to investigate links between the diathesis-stress hypotheses of the quadripartite model and the helplessness-hopelessness theory of depression. Simultaneously the study tested the psychometric properties of the Turkish version of the Learned Helplessness Scale (LHS). To this end, the LHS was initially administered to a pilot sample consisting of 440 college students. Next, the LHS, Beck Hopelessness Scale (BHS), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Pittsburgh Sleep Quality Index (PSQI), Generalised Self-Efficacy Scale (GSES), and Rosenberg Self-Esteem Scale (RSES) were administered to 191 college students. Factor structures extracted from the data on the initial sample was tested on the validation sample and a three-factor structure containing "Internal and Stable Appraisals", "Losing Control" and "General Helplessness" was confirmed. Considering the differentiation between anxiety and depression along with the hypothesis of helplessness-hopelessness theory, it appeared that hopelessness and poor self-esteem constituted specific dimensions of depressive symptomatology. Poor sleep quality was a non-specific component of both anxiety and depression. Helplessness was strongly associated with low self-worth. The results of the present study are discussed in light of quadripartite and helplessness-hopelessness models of depression.